Maternal reactions and feelings towards the hospitalization of the child in a Neonatal Intensive Care Unit: a narrative literature review (Research, Society and Development, 2022)
Introduction: There is an intrinsic social pressure placed on women's lives in relation to motherhood and, therefore, when the gestation period does not end as expected, there is a great impact on the family environment and, especially, on the mother-baby relationship. Objectives: to elucidate the conceptions regarding the feeling of motherhood in the face of the hospitalization of the neonate in intensive care, seeking to establish challenges and learning related to the scope. Methodology: This is a descriptive research of the type narrative review of the literature. The research was carried out through online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases. Information Services. Results and discussion: The high complexity of procedures performed in the Intensive Care Unit (NICU) restricts the visiting hours and physical contact so expected by the pregnant woman and, therefore, the hospitalization of a newborn (NB) in the neonatal ICU demands the reorganization of a new routine for the newborn's family. In this way, the family dynamics is altered and arouses several feelings in the puerperal woman, such as anxiety due to early separation, failure, insecurity, concern and decreased or even lack of confidence in the ability to care for her child. This experience lived by the mother can trigger the emergence of depression, anxiety disorders, fatigue and sleep disorders, affecting the family bond. Final considerations: With this, it is noted that the hospitalization of an NB impacts the idealized expectations of the child's birth. Thus, the communication of the hospital's multidisciplinary team with the baby's family is extremely important for the construction of the family's autonomy.